Effect of normal aging on the structure of marginal division of neostriatum as measured by MR phase imaging and diffusion tensor imaging. Issue 5 (13th September 2016) - Chen, Zhiye; Liu, Mengqi; Liu, Mengyu; Li, Jinfeng; Shan, Han; Liu, Shuangfeng; Lou, Xin; Shu, Siyun; Ma, Lin
Abstract : Purpose: To investigate the structural changes of marginal division (MrD) which is the high intensity zone between globus pallidus and putamen on phase image in the human brain. Materials and Methods: The structural changes of MrD were investigated based on MR phase imaging and diffusion tensor imaging (DTI) data at 3.0 Tesla (T) MR scanner in 72 volunteers. Phase value, including high iron components (HIC), low iron components (LIC), LIC ratio, and average iron components (AIC), were obtained using histogram analysis about the head of caudate nucleus (CA), globus pallidus (GP), putamen (PU), and MrD. The structural measurement of MrD was applied on corrected phase images (CPIs). Average apparent diffusion coefficient (ADC) values and fractional anisotropy (FA) values were calculated based on DTI data. Results: MrD showed negative correlation for LIC with aging, with the highest HIC (left/right 2149.3 ± 19.6/2155.9 ± 17.9) and LIC (left/right 1996.6 ± 18.2/1999.6 ± 20.7), the lowest LIC ratio (left/right 21.5% ± 7.9%/19.4% ± 8.0%), and the highest AIC (left/right 2116.4 ± 21.4/2124.7 ± 21.0). The width (Head: left/right 2.01 ± 0.41 mm/1.86 ± 0.36 mm; Body: left/right 1.84 ± 0.38 mm/1.49 ± 0.29 mm; Tail: left/right 1.17 ± 0.36 mm/1.05 ± 0.23 mm) and area (left/right 49.44 ± 9.71 mm 2 /42.75 ± 8.80 mm 2 ) of MrD showed negative correlation with aging, presenting gradually narrower pattern based on CPIs. Average ADC value (left/right 0.69 ± 0.04 10 ‐3 mm 2 /s / 0.71 ± 0.03 10 ‐3 mm 2 /s) revealed negative correlation, while FA value (left/right 0.19 ± 0.03/0.22 ± 0.03) revealed positive correlation with aging. Conclusion: The findings suggested that the structure measurements based on CPIs and DTI could provide a simple and effective tool for the evaluation of MrD in vivo in the human brain and for the assessment of the changes seen with aging. Level of Evidence : 1 J. MAGN. RESON. IMAGING 2017;45:1343–1351